Development of a Measure on Substance use and Pictorial warnings - Reeves Wesley, J.; Rajesh, B. (Journal of Contemporary Research in Management (JCRM), 2013)
Substance use is a pressing problem in any society at large and ways to mitigate substance use among users have been discussed in various forums globally. Review of prior literature indicates that research on substance use has been extensively done. Measures suggested are to imprint pictorial signs that depict the ill effects of tobacco use. Studies on the effect of pictorial warnings on tobacco use have been scarcely done and instruments to measure the use of substance, pictorial warnings and its effects are also scarce in India. This study makes an attempt to develop validate and test for reliability a questionnaire to measure substance use, effects of pictorial warnings on substance use. The data is collected from 53 students.